(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Retinal damage due to the blunt eye injury is often the cause of vision loss. Purpose. To develop the classification algorithm to determine the severity of the foveal structural changes in patient after blunt eye injury using spectral optical coherence tomography (SOCT). Material and Methods. We observed 43 patients after blunt eye injury, all of them underwent SOCT. Results. It is important to determine the state of two morphological characters — ellipsoid of internal segments of photoreceptors, the outer limiting membrane using SOCT. It allows to determine the severity of structural foveal changes using SOCT. Conclusion. The classification algorithm is found. It allows to determine the severity of structural foveal changes after blunt eye injury.